Tanzawaic acids I–L: Four new polyketides from Penicillium sp. IBWF104-06 - Sandjo, Louis P.; Thines, Eckhard; Opatz, Till; Schüffler, Anja (Beilstein Journal of Organic Chemistry, 2014)
Four new polyketides have been identified in culture filtrates of the fungal strain Penicillium sp. IBWF104-06 isolated from a soil sample. They are structurally based on the same trans-decalinpentanoic acid skeleton as tanzawaic acids A–H. One of the new compounds was found to inhibit the conidial germination in the rice blast fungus Magnaporthe oryzae at concentrations of 25 μg/mL.
Keywords: arohynapene; natural products; polyketides; structure elucidation; tanzawaic acid

(untitled) - Kuramoto, M.; Yamada, K.; Shikano, M.; Yazawa, K.; Arimoto, H.; Okamura, T.; Uemura, D. (Chem. Lett., 1997)

(untitled) - Malmstrøm, J.; Christophersen, C.; Frisvad, J. C. (Phytochemistry, 2000)

(untitled) - Masuma, R.; Tabata, N.; Tomoda, H.; Haneda, K.; Iwai, Y.; Omura, S. (J. Antibiot., 1994)

(untitled) - Arimoto, H.; Nishimura, K.; Kuramoto, M.; Uemura, D. (Tetrahedron Lett., 1998)

(untitled) - El-Neketi, M.; Ebrahim, W.; Lin, W.; Gedara, S.; Badria, F.; Saad, H.-E. A.; Lai, D.; Proksch, P. (J. Nat. Prod., 2013)

(untitled) - Houbraken, J.; Frisvad, J. C.; Samson, R. A. (Stud. Mycol., 2011)

(untitled) - Tabata, N.; Tomoda, H.; Iwai, Y.; Omura, S. (J. Antibiot., 1993)

(untitled) - Tabata, N.; Tomoda, H.; Masuma, R.; Haneda, K.; Iwai, Y.; Omura, S. (J. Antibiot., 1993)

(untitled) - Tabata, N.; Tomoda, H.; Iwai, Y.; Omura, S. (J. Antibiot., 1995)

(untitled) - Lippke, G.; Thaler, H. (Starch/Staerke, 1970)

(untitled) - Schüffler, A.; Kautz, D.; Liermann, J. C.; Opatz, T.; Anke, T. (J. Antibiot., 2009)

(untitled) - Anke, H.; Bergendorff, O.; Sterner, O. (Food Chem. Toxicol., 1989)

(untitled) - Zapf, S.; Hoßfeld, M.; Anke, H.; Velten, R.; Steglich, W. (J. Antibiot., 1995)

(untitled) - Kettering, M.; Valdivia, C.; Sterner, O.; Anke, H.; Thines, E. (J. Antibiot., 2005)